Upaya Meningkatkan Hasil Belajar Keterampilan Passing Bawah Bola Voli Menggunakan Pendekatan Teaching at The Right Level (TaRL) - Yusup Mahendra; Reshandi Nugraha; Regi Dwi Septian (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This research is motivated by the low learning outcomes of volleyball underhand passing skills caused by differences in student abilities that have not been fully accommodated in the learning process. The study aims to determine efforts to improve learning outcomes in volleyball underhand passing skills through the application of the Teaching at the Right Level (TaRL) approach. The study used the Classroom Action Research (CAR) method, implemented in two cycles with the stages of planning, action, observation, and reflection. The research subjects were 36 eighth-grade students of YASPRI MARIPARI Sukawening Junior High School. The research instrument used the AAHPER Face Wall-Volley Test to measure underhand passing skills. Data analysis was performed using descriptive statistics, the Shapiro–Wilk normality test, the Wilcoxon Signed Rank Test, and the N-Gain test. The results showed an increase in learning outcomes in each cycle. The average student score increased from 8.58 in the pretest to 9.97 in Cycle I and 11.67 in Cycle II. The Wilcoxon test results showed a significance value of 0.000 (<0.05), indicating a significant improvement in learning outcomes. Learning effectiveness was also demonstrated by the N-Gain value of 0.4449, categorized as moderate. The learning completion percentage increased from 19.4% in the initial conditions to 88.9% in Cycle II. Based on the research results, it can be concluded that the Teaching at the Right Level (TaRL) approach is effective in improving learning outcomes in volleyball underhand passing skills through learning tailored to the students' ability levels, making the learning process more adaptive and able to accommodate differences in ability within the class. Keywords: Volleyball, Learning Outcomes, Underhand Passing, Physical Education, Teaching at the Right Level (TaRL).